Role of erythropoietin in anemic children with chronic renal failure in Diyala Governorate, Iraq (Journal of Ideas in Health, 2024)
Background: Chronic conditions, such as anemia are often attributed to insufficient production of erythropoietin. This study focuses on evaluating the effectiveness and safety of recombinant erythropoietin therapy in managing anemia associated with chronic kidney disease. Methods: A prospective cross-sectional study was conducted on 40 patients diagnosed with anemia due to chronic kidney disease. The study took place from August 1, 2022, to February 30, 2023, at Al-Batool Teaching Hospital in Diyala Province, Iraq. The participants were divided into two groups: the first group comprised 30 patients aged between 80 days and 15 years receiving conservative treatment, while the second group included 10 patients aged 6 to 13 years undergoing hemodialysis. Data analysis, including descriptive and bivariate methods, was performed using SPSS Version 20, with a p-value of less than 0.05 considered statistically significant.Results: In this study, group I patients had a mean age of 7.1 years, with two-thirds (66.6%) falling within the 1–10 age range and a male-to-female ratio of 1.7:1. In group II, the mean age was 9.5 years, with 60% in the 5–10 age group and a balanced gender ratio (1:1). The primary causes of chronic renal failure (CRF) in Group I were cystinosis and reflux nephropathy (26.7% each), while laboratory findings revealed a mean glomerular filtration rate (GFR) of 72.19 mL/min and severe anemia with hemoglobin (Hb) levels of 4.7 g/dL before treatment. Treatment significantly improved Hb levels in Group I (7.47 to 10.17 g/dL, P < 0.001) but showed limited efficacy in Group II (6.9 to 8.2 g/dL, P = 0.002).Conclusion: The findings underscore variable treatment responses between groups, emphasizing the need for tailored anemia management strategies.
Keywords: Erythropoietin, Anemia, Children, Chronic Renal Failure, Glomerular Filtration Rate, Iraq